Japanese Women and Sport : beyond baseball and sumo - Kietlinski, Robin (London : Bloomsbury Academic, 2011)
Annotation In 'Japanese Women and Sport', Robin Kietlinski sets out to problematize the hegemonic image of the delicate Japanese woman, highlighting an overlooked area in the history of modern Japan. Previous studies of gender in the Japanese context do not explore the history of female participation in sport, and recent academic studies of women and sport tend to focus on Western countries. Kietlinski locates the discussion of Japanese women in sport within a larger East Asian context and considers the socio-economic position and history of modern Japan. Reaching from the early 20th century to the present day, Kietlinski traces the progression of Japanese women's participation in sport from the first female school for physical education and the foundations of competitive sport through to their growing presence in the Olympics and international sport
Introduction : Why women's sport? Why Japan? -- Japanese sportswomen in context -- The road to participation in competitive sport -- From calisthenics to competition : early participation in international sport -- From antipathy to applause : the emergence of female powerhouses on the international scene -- Progress and potential : sportswomen in the 1960s and 1970s -- Female athletes in contemporary Japan -- Theoretical concerns surrounding Japanese women in sport -- Afterword : What about women's baseball and women's sumo?